EFFECT OF TALKING STICK LEARNING MODEL TO STUDENT LEARNING OUTCOMES ON GASOLINE ENGINE COURSE IN CLASS X OF TSM SMKN 1 PALANGKA RAYA ACADEMIC YEAR 2016/2017 - Pras Digantara; Wiyogo (Jurusan Pendidikan Teknologi Dan Kejuruan, 2018)
Problems in class X TSM in SMKN 1 Palangka Raya in learning system conducted by teachers were ineffective learning model. Effective learning in school is very difficult to apply especially on gasoline engine subject because it has a lot of explanations including Explanation of combustion motor that includes type and working principle of motor fuel so that students consider motor fuel material is difficult to be understood. The learning alternative that can improve students' learning motivation is with the learning model talking stick The purpose of this study is to determine the effect of talking stick model on student learning outcomes on the material motor fuel class X TSM at SMKN 1 Palangka Raya Year Teaching 2016/2017. The research used experimental research consisting of two classes namely TSM A experimental class by using talking stick teaching model which is 16 students and TSM B control class using learning model of lecture which amounted to 16 students, at SMKN 1 Palangka Raya. In the data after the research conducted post test group experimental results and control group of hypothesis test data in can Tcount = 5,10 > ttable = 2,042 at a significant level 5% = 0,05 and dk = (16 + 16 - 2) = 30. Visible tcount ttable, then Ho rejected and HIbe accepted. So it can be concluded that there is influence of student learning outcomes taught by using the model of talking stick learning on the material of cars fuel class X TSM SMKN 1 Palangka Raya academic year 2015/2016